(untitled) (European Journal of Interdisciplinary Research and Development, 2025)
This article explores the significant role of the Constitution in social life. It analyzes the Constitution’s fundamental status as the supreme law of the state, its core function within the legal system, and its role in ensuring reform, openness, and modernization. The article also highlights the Constitution’s contribution to promoting democracy, the rule of law, and social progress, focusing on its historical background, basic principles, and specific functions. Through a comparison of constitutions from different countries, the article reveals the essential differences between China’s governance under the Constitution and Western constitutionalism. Finally, it emphasizes that the Constitution is a critical guarantee for political stability, the improvement of the legal system, and social harmony.